Usage of Artificial Intelligence among Research Scholars at Higher Education Level - Rukhsar Mughal; Muhammad Qassim, Fatima (JCTE, 2026)
This study explores the usage of Artificial Intelligence usage among research scholars in higher education, emphasizing critical thinking, creativity, and academic productivity. It addresses rising concerns about AI tools such as ChatGPT, Grammarly, and Mendeley potentially undermining cognitive autonomy and the scholarly integrity of academic work. While these tools assist with literature review, academic writing, and data analysis, excessive reliance may weaken higher-order thinking and independent problem-solving skills. A quantitative research approach, guided by the Artificial Intelligence in Education (AIED) theoretical framework, was adopted using a descriptive research design. The study surveyed 136 eighth-semester students from the B.Ed. and BS Health & Physical Education programs at the National University of Modern Languages, Islamabad, and the International Islamic University, Islamabad, Pakistan. Data were collected using a self-developed 21-item questionnaire based on a 5-point Likert scale, assessing students’ perceptions across three core domains: Cognitive Enhancement and Analytical Thinking, Creativity and Idea Development, and Academic Writing and Productivity. Data analysis was conducted using descriptive statistics and independent sample t-tests through SPSS. The findings revealed moderate to high AI usage, with participants generally reporting favorable perceptions of AI’s role in supporting their cognitive and academic tasks. Nevertheless, the statistical findings showed that there were no significant differences in cognitive impact according to academic discipline or gender and thus the null hypothesis was retained. The report finds that AI can positively impact academic performance without reducing cognitive autonomy when utilized in a responsible manner. However, the moral aspect of use and overreliance raises the issue of formal AI literacy. It proposes the inclusion of AI ethics and critical engagement strategies in higher education.